2019
DOI: 10.1371/journal.pone.0222754
|View full text |Cite|
|
Sign up to set email alerts
|

A matter of taste: Spatial and ontogenetic variations on the trophic ecology of the tiger shark at the Galapagos Marine Reserve

Abstract: Sharks are top predators across ocean food webs and have a major ecological role in marine ecosystems. Investigating the trophic ecology of this group of species is thus essential to understand ecosystem functioning and inform specific management actions aimed at shark conservation. The Galapagos Islands represent one of the last ocean wildernesses, where populations of sharks and other top marine predators come close to a pristine status. Here we provide the first study on the trophic ecology of the tiger sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Our review confirmed that this ecosystem supports a large and diverse cetacean community, but beyond presence and distribution information, for most species not much more is known about habitat use, population structure, health, and social ecology. In contrast, significantly more efforts have been devoted to the study and monitoring of Galaṕagos invertebrates (e.g., Edgar et al, 2004;Edgar et al, 2008;Edgar et al, 2011), fishes (e.g., Schiller et al, 2014;Lamb et al, 2018;Salinas-de-Leoń et al, 2019), pinnipeds (e.g., Paéz-Rosas et al, 2012;Brock et al, 2013a;Brock et al, 2013b;Paeź-Rosas et al, 2016;Paéz-Rosas et al, 2018;Urquıá and Paéz-Rosas, 2019;Paéz-Rosas et al, 2021), and seabirds (e.g., Anchundia et al, 2014;Tompkins et al, 2017;Jimeńez-Uzcategui et al, 2019;Arauco-Shapiro et al, 2020). Admittedly, cetacean research is comparatively more expensive and more logistically demanding.…”
Section: Discussionmentioning
confidence: 99%
“…Our review confirmed that this ecosystem supports a large and diverse cetacean community, but beyond presence and distribution information, for most species not much more is known about habitat use, population structure, health, and social ecology. In contrast, significantly more efforts have been devoted to the study and monitoring of Galaṕagos invertebrates (e.g., Edgar et al, 2004;Edgar et al, 2008;Edgar et al, 2011), fishes (e.g., Schiller et al, 2014;Lamb et al, 2018;Salinas-de-Leoń et al, 2019), pinnipeds (e.g., Paéz-Rosas et al, 2012;Brock et al, 2013a;Brock et al, 2013b;Paeź-Rosas et al, 2016;Paéz-Rosas et al, 2018;Urquıá and Paéz-Rosas, 2019;Paéz-Rosas et al, 2021), and seabirds (e.g., Anchundia et al, 2014;Tompkins et al, 2017;Jimeńez-Uzcategui et al, 2019;Arauco-Shapiro et al, 2020). Admittedly, cetacean research is comparatively more expensive and more logistically demanding.…”
Section: Discussionmentioning
confidence: 99%
“…Similar correlations of foraging habitat density and TEST have been observed in grizzly bears ( Ursus arctos ), in which bears living in coastal habitats with high conspecific overlap for spatially constrained salmon resources also had the highest TEST levels when compared to more dispersed, generalist bears (Bryan et al., 2013). It should also be noted that, specific to the Galapagos archipelago, the highest abundance of shark species which prey on sea lions are found around near‐shore islets and seamounts (Acuña‐Marrero et al., 2018; Salinas‐de‐León et al., 2019), strongly overlapping with the foraging areas of benthic divers. TEST is a known inhibitor of apprehension toward predators in a variety of contexts (King et al., 2005; Wingfield et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For 18 sharks captured and fitted with satellite tags between 2014–2015, the satellite data used in this study was obtained from Acuña-Marrero et al (reference [23] of the article [ 1 ]), as indicated in the table caption. For five sharks captured and tagged with satellite tags between 2016–2017, satellite data were newly collected.…”
mentioning
confidence: 99%
“…For five sharks captured and tagged with satellite tags between 2016–2017, satellite data were newly collected. For 18 sharks captured and tagged with acoustic tags between 2014–2015, the acoustic data used in this study is a combination of re-used data collected 2014–2015 (obtained from Acuña-Marrero et al, reference [23] of the article [ 1 ]) and new data detected by the acoustic receiver array September 2015-October 2017. For 10 sharks captured and tagged with acoustic tags between 2016–2017, acoustic data were newly collected.…”
mentioning
confidence: 99%
See 1 more Smart Citation